Assessment of non-timber forest products utilization in Kwabaktina forest reserve, Adamawa State, Nigeria - Nguuma, Sambe Leoskali; Ngunan, Ver Priscilla; Alumun, Aondoakaa Mathew; Vahya, Pembi (Journal of Forests, 2025)
This study assessed non-timber forest products utilization in Kwabaktina Forest Reserve, Hong Local Government Area of Adamawa State. Data were collected through semi-structured questionnaires, field observations, personal interviews, and focused group discussions. Descriptive and inferential statistics were used to analyze the data. The majority (54.6%) of the respondents were female, and most were youths (44.3%) between the ages of 18 to 40 years. A greater proportion (63.3%) were married individuals with a low level of education in the study area. The findings revealed that most of the respondents (72.25%) belonged to the household size category of 1-10 and were low-income earners. The findings also identified some available NTFPs in the study area, which include Borassus fruit, Borassus bark, honey, moringa seed, leaves, bush meat, caterpillars, crickets, and Borassus hypocotyls. Hypocotyls were the most preferred NTFPs utilized by the people. The results revealed that NTFPs were utilized to a very high extent due to the high economic value of the products. Gender played a significant role in the utilization of NTFPs, while age, educational status, and household size significantly determined the utilization of NTFPs in the study area. The results also showed no significant difference in the extent to which people utilized NTFPs. The study found that non-timber forest products (NTFPs) provided significant food, employment, income, and livelihood sources in the study areas. The study recommends prioritizing financial and technical support for alternative income-generating ventures, stakeholder involvement in forest resource planning, and economic evaluations of NTFP utilization to optimize their benefits.